Addressing complexity for educating the future-ready workforce in STEM fields: MINTco@NRW from a mathematics educational perspective - Stoffels, Gero; Schäfer, Julia; Köster, Jacqueline; Witzke, Ingo (LUMAT: International Journal on Math, Science and Technology Education, 2025)
Educating the future-ready workforce in STEM fields is complex. This is demonstrated by numerous publications in the context of the fourth industrial revolution, the 21st century skills, and the development of integrated models in STEM Education. In this article, this complexity is first addressed on a theoretical level by reviewing developments in the world of work and the associated challenges for General Didactics and Subject Specific Education. A synthesis of the contrasting perspectives shows that empirical research requires sufficiently complex settings. With MINTco@NRW, such a setting is presented, and its complexity characteristics are identified. In addition, insights are provided into the research perspectives associated with the project. They are mathematical-relatedness, students’ self-efficacy and the mentoring of STEM problem solving. Research questions that arise are in the contexts of performance assessments in such settings and teacher training to provide the necessary skills to make learners future-ready. The conclusion is that integrated STEM education for a future-ready workforce requires scientific approaches that make fruitful use of the mentioned complexities.